Resonance effects in the Raman scattering of monolayer and few-layer MoSe2 - Soubelet, Pedro Ignacio (2016)
Using resonant Raman scattering spectroscopy with 25 different laser lines, we describe the Raman scattering spectra of monolayer and multilayer 2H-molybdenum diselenide (MoSe2) as well as the different resonances affecting the most pronounced features. For high-energy phonons, both A- and E-symmetry type phonons present resonances with A and B excitons of MoSe2 together with a marked increase of intensity when exciting at higher energy, close to the C-exciton energy. We observe symmetry-dependent exciton-phonon coupling affecting mainly the low-energy rigid layer phonon modes. The shear mode for multilayer displays a pronounced resonance with the C exciton while the breathing mode has an intensity that grows with the excitation laser energy, indicating a resonance with electronic excitations at energies higher than that of the C exciton.